Determinants of inflation and impact of selected Macro variable on Inflation in Nepal (The Nepalese Management Review, 2024)
This paper aimed to identify the impact of selected macro variable on inflation and examining the relationship between inflation rate and selected macro variables. Generally, both fiscal and monetary policies seek at achieving relative macroeconomic stability through stable prices or low and stable inflation. In the light of this, this study empirically investigates the impact of some macro variable on inflation in Nepal with the use of econometric technique multiple regression, correlation and trend analysis using time series data from 2001 to 2018. The annual data is collected from Nepal Rastra Bank and web site of World Bank. The result revealed that money supply is positively correlated with inflation, but the result is however insignificant in the case of GDP growth rate and to determine the inflation rate in context of Nepal. The regression analysis indicates that 85.9% of inflation rate is determined by exchange rate, money supply, GDP, per capita income and inflation rate of India, rest in 14.1% inflation rate is determined by other factors. The study found that there is positive correlation between exchange rate and inflation rate, money supply and inflation, per capita income and inflation rate and Indian inflation and inflation rate of Nepal. But study also revealed that insignificant negative correlation between GDP and inflation rate of Nepal. The exchange rate, money supply and Indian inflation are significant with inflation but GDP and per capita income are insignificant with inflation over the time period under study. There is only the monetary policy is not capable to control inflation, the fiscal measure are highly effective to controlling government expenditure, personal expenditure and private & public investment. The study therefore recommends that the central bank of Nepal need to deal with monetary and fiscal policy in more transparent manner so as to address the issue of inflation in Nepal.